Backstepping control based on L1 adaptive theory for large transport aircraft heavy load airdrop. (5th January 2018) - Zhang, Pengchao
A study of the L 1 adaptive controller is conducted based on the backstepping method for the model of large transport aircraft with drastic changes appearing in heavy load airdrop process. The system is divided into an attitude subsystem and a velocity subsystem. For the attitude subsystem, the backstepping control is used to design the virtual control of path angle and the pitch angle in external loop with the L 1 adaptive controller designed in internal loop to estimate the uncertainties and disturbances in the subsystem and to compensate them. In the stability analysis, the uniform boundedness of all signals in the closed-loop system is proven. Simulation results show that the proposed control method preserves the quick dynamic torque response, high efficiency, and robustness in heavy load airdrop; to some extent it can alleviate the control switch lead or lag problem and ensure the safety of the transport aircraft to fulfill the complete airdrop mission.